Performance survey on a new standardized formula for oral signal suppression in MRCP. (2018) - Frisch, Anne; Walter, Thula C.; Grieser, Christian; Geisel, Dominik; Hamm, Bernd; Denecke, Timm
Highlights: Recently, a new biological standardized product for MRCP became available. The product is considered effective as oral signal suppressor in T2-w images. Obtained MRCP imagery show a good image quality. Patients' feedback on taste and palatability is very high. Abstract: Background: Orally administered substances, which reduce image contamination by overlying gastrointestinal fluid signals, can be used to enhance the quality of MRCP images. Recently, a new standardized formula consisting of biological substances has become available. The objective of this study is to provide a first assessment of achievable MRCP image quality, taste and palatability of this new dedicated agent. Methods: In January 2015 to May 2015 practicing radiologists in Germany, Austria and Switzerland were asked to evaluate image quality as well as taste and palatability when using the new agent (LumiVision ® ; b.e. imaging; Baden-Baden; Germany) in MRCP questionnaire. Both criteria were rated with a 6-point Likert scale ranging from "1" (best) to "6" (worst). Results: A total 185 of 475 radiologic institutions (39%) submitted feedback on image quality, 187 (39%) on the taste/palatability. Assessments of image quality regarding presence of disturbing gastrointestinal fluid signal resulted in a median of 2. The majority of patients rated the subjective taste as very good (median of 1). No side effects of relevance were recorded. Conclusion: This large survey shows that the tested product is considered effective by radiologists regarding MRCP image quality. Patients' feedback on taste and palatability was very positive.